Analisis Penyebab Pending Klaim Berkas BPJS Kesehatan Pelayanan Pasien Rawat Inap Di Rumah Sakit X - Larasty, Gevi; Farhansyah, Fani; Anisa, Desfa (Shofanah Media Berkah, 2023)
BPJS Health claim files for Quarter 1 January, February and March 2023 with 129 BPJS health claim files for the most important inpatient services. The reason for the return was because it did not pass the service administration verification, the difference in diagnosis coding between the BPJS coder and the hospital diagnosis code and the incompleteness of the claim file. So the settlement of claims results in pending claims which disrupt the hospital's financial flow. The aim of this research is to find out the most important BPJS Health file claims for inpatient services at Hospital The results of this research are the percentage of factors causing pending BPJS health claims for inpatient services based on the suitability of membership administration, namely 100%. The percentage of factors causing pending BPJS health claims for inpatient services based on suitability of service administration is 91.6% appropriate and 8.4% inappropriate. And the percentage of factors that cause pending BPJS health claims for inpatient services based on suitability of health administration is 94.7% appropriate and 5.3% inappropriate.